The correlation between serum MHR and NLR and the severity of coronary lesions in NSTE-ACS patients of different genders - Yang, Yanping; Lv, Xiaobing; Tan, Kai; Li, Kai; Li, Shaohua; Meng, Xia; Chen, Yunyun; Wang, Fuqing; Xin, Hui (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTo study the relationship between the monocyte/high-density lipoprotein cholesterol ratio (MHR) and neutrophil-to-lymphocyte ratio (NLR) and coronary artery stenosis in Non-st-elevation acute coronary syndromes (NSTE-ACS) patients of different genders.MethodsA total of 253 control and 800 NSTE-ACS patients were included, and clinic data (29 items) were also collected. NSTE-ACS patients were divided into low-risk (0–23) and high-risk (≥ 23) groups based on the Synergy between PCI with Taxus and Cardiac Surgery (SYNTAX) score. Then, Spearman correlation and multivariate logistic regression analyses were performed to study the associated factors of high-risk SYNTAX score in male and female NSTE-ACS patients, respectively. Finally, the receiver operating characteristic (ROC) curve was used to calculate the diagnostic value of MHR and NLR for predicting high-risk SYNTAX scores in male NSTE-ACS patients.ResultsSixteen distinct factors differed between the high- and low-risk groups in male NSTE-ACS patients, a significantly higher number than female NSTE-ACS patients. Gout/hyperuricemia, smoking, NLR, and MHR are independent risk factors for arterial stenosis. At the same time, high-density lipoprotein and left ventricular ejection fraction (LVEF) are found to be protective factors in male NSTE-ACS patients. Fibrinogen, apolipoprotein B/A, and neutrophils are identified as independent risk factors for arterial stenosis in female NSTE-ACS patients, while LVEF and high-density lipoprotein are protective factors. Finally, combined NLR and MHR [p = 0.000, 95% confidence interval (CI) = 0.726–0.810] had better predictive efficacy on the degree of arterial vessel stenosis than NLR or MHR alone. The sensitivity and specificity of the ROC curve were 0.672 and 0.769, respectively.ConclusionThe combination of MHR and NLR shows potential for predicting and assessing the severity of coronary artery stenosis in male patients with NSTE-ACS.